Different platforms, different uses: testing the effect of platforms and individual differences on perception of incivility and self-reported uncivil behavior. Issue 2 (10th January 2023) - Sude, Daniel J; Dvir-Gvirsman, Shira
Abstract: Two large surveys with adult samples of Americans ( N = 1, 105; N = 1, 035) investigated differences in perceived incivility between seven social media platforms. Perceptions of incivility were targeted, given both their inherent societal relevance and the personalized nature of each user's platform experience. Utilizing a novel approach, observations per platform were nested within each user, facilitating disentangling user-level from platform-level factors. Study 1 demonstrated that even accounting for differences between users, perceptions vary by platform. Further, while individual users do admit to generating uncivil content themselves, self-perceptions were in contrast largely stable across platforms. Study 2 built upon Study 1 by investigating additional platform-level factors that could impact perceptions of incivility: Differences in perceived affordances between platforms were related to differences in perceptions of incivility's prevalence. Specifically, platforms characterized by either perceived anonymity or perceived network association were in turn perceived to be more uncivil. Lay Summary: It can seem like Americans are increasingly rude, insulting, and hateful toward one another, particularly online. Perceptions of incivility in turn can have a variety of impacts, including undermining Americans' faith in each other, interpersonally and politically. Rather than focus on social media generally, in this article, two large surveys examined separate social media platforms. The first study found that American users do see certain platforms as more uncivil than others, even taking into account differences in their behavior. The same user behaving similarly on two different platforms may still see differences between these platforms. Interestingly, users did not just think that others were uncivil but also admitted to behaving uncivilly. The second study asked what it was about the platforms that might differ, leading to differences in impressions of incivility. Specifically, it found that platforms perceived to have more network association were perceived to have more incivility. Further, it found that platforms that were perceived to allow greater anonymity were perceived to have more incivility. In other words, users likely felt that incivility was more likely when platforms (a) had a sense of community as well as (b) where people could escape personal consequences for their uncivil behavior.